Is strength of handedness reliable over repeated testing? An examination of typical development and autism spectrum disorder - Scharoun, Sara M.; Bryden, Pamela J. (Frontiers in Psychology, 2015)
Despite a lack of agreement concerning the age at which adult-like patterns of handedness emerge, it is generally understood that hand preference presents early in life and development is variable. Young children (ages 3–5 years) are described as having weak hand preference; however, older children (ages 7–10 years) display stronger patterns. Here, strength of hand preference refers to reliable use of the preferred hand. In comparison to their typically developing (TD) peers, individuals with autism spectrum disorder (ASD) are described as having a weak hand preference. This study aimed to extend the literature to assess three measures of handedness (Waterloo Handedness Questionnaire – WHQ, Annett pegboard – AP, and WatHand Cabinet Test – WHCT) in two repeated sessions. The first research question aimed to delineate if the strength of hand use changes across testing sessions as a function of age in typical development. Right-handed children reported a reliable preference for the right hand on the WHQ, similar to adults. A marginally significant difference was revealed between 3- to 4- and 5- to 6-year-olds on the AP. This was attributed to weak lateralization in 3- to 4-year-olds, where the establishment of hand preference by age 6 leads to superior performance with the preferred hand in 5- to 6-year-olds. Finally, for the WHCT, 3- to 4-year-olds had the highest bimanual score, indicating use of the same hand to lift the cabinet door and retrieve an object. It is likely that the task was not motorically complex enough to drive preferred hand selection for older participants. The second research question sought to determine if there is difference between (TD) children and children with ASD. No differences were revealed; however, children with ASD did display variable AP performance, providing partial support for previous literature. Findings will be discussed in light of relevant literature.